Achieving a high open-circuit voltage in inverted wide-bandgap perovskite solar cells with a graded perovskite homojunction. (July 2019) - Chen, Cong; Song, Zhaoning; Xiao, Chuanxiao; Zhao, Dewei; Shrestha, Niraj; Li, Chongwen; Yang, Guang; Yao, Fang; Zheng, Xiaolu; Ellingson, Randy J.; Jiang, Chun-Sheng; Al-Jassim, Mowafak; et al.
Abstract: Wide-bandgap (∼1.7–1.8 eV) perovskite solar cells have attracted substantial research interest in recent years due to their great potential to fabricate efficient tandem solar cells via combining with a lower bandgap (1.1–1.3 eV) absorber (e.g., Si, copper indium gallium diselenide, or low-bandgap perovskite). However, wide-bandgap perovskite solar cells usually suffer from large open circuit voltage ( V oc ) deficits caused by small grain sizes and photoinduced phase segregation. Here, we demonstrate that in addition to large grain sizes and passivated grain boundaries, controlling interface properties is critical for achieving high V oc 's in the inverted wide-bandgap perovskite solar cells. We adopt guanidinium bromide solution to tune the effective doping and electronic properties of the surface layer of perovskite thin films, leading to the formation of a graded perovskite homojunction. The enhanced electric field at the perovskite homojunction is revealed by Kelvin probe force microscopy measurements. This advance enables an increase in the V oc of the inverted perovskite solar cells from an initial 1.12 V to 1.24 V. With the optimization of the device fabrication process, the champion inverted wide-bandgap cell delivers a power conversion efficiency of 18.19% and sustains more than 72% of its initial efficiency after continuous illumination for 70 h without encapsulation. Additionally, a semitransparent device with an indium tin oxide back contact retains more than 88% of its initial efficiency after 100 h maximum power point tracking. Graphical abstract: Image 1 Highlights: Guanidinium bromide treatment to tune the doping properties of perovskite films. Formation of a graded perovskite homojunction enhances built-in electric field. Enhancement of open-circuit voltage from 1.12 to 1.24 V after the treatment. Inverted wide-bandgap perovskite solar cells deliver a maximum efficiency of 18.19%.